TRANSFORMATION OF LOCAL GOVERNMENTS IN THE CRISIS OF MODERNITY AND NEW CIVILISATION DEBATES - Can, Mehmet; Güneş, İskender (Journal of Oriental Studies, 2024)
Today, the world is on the brink of a crisis that has plunged it into the darkness of the Middle Ages. The crisis of modernity raises serious questions about the sustainability of existing social, economic and political systems. In this context, the basic principles for the construction of a new civilisation are being determined and a global intellectual struggle is taking place. The crisis of modernity points not only to a material but also to a spiritual impasse. Societies are facing various problems and struggling with difficulties arising from existing paradigms. Therefore, to create a new vision of civilisation is to lay the foundations for a sustainable, just and human-oriented future. In this struggle, it is important to treat diversity not as a threat, but as an asset. Diverse cultures, worldviews and ways of life should be recognised as the cornerstones of a new civilisation. Not only economic growth, but also universal values such as human rights, environmental protection, equality and justice should be central to discussions on a new civilisation. This will enable the adoption of a human-centred approach and sustainable solutions to global and local problems. In conclusion, an intellectual effort is required to deal with the crisis of modernity and to build a new civilisation. This effort should include bringing together different perspectives, seeing diversity as richness and cooperating for a common future. Keywords: Modernity, Crisis, Civilisation, Local Government